Rescuing the fact-insensitivity thesis - Costa, Claiton Silva da (2024)
This thesis explores the debates surrounding G.A. Cohen’s fact-insensitivity thesis. I argue that, so long we take for granted either the counterfactual theory of explanation aligned with fictionalism about grounding or unificationism about explanation, we have a favorable outcome for his thesis. In the first part I challenge, without any big assumption, some the critiques the thesis received in the literature and all the attempts to defend it from the critiques. In the second part I explore the logical consequences of some theories of explanation (CTE and unificationism) for Cohen’ thesis. I demonstrate that the former is wanting to deal with a regress problem, but not the latter. I conclude that, in the light of unificationism, Cohen’s thesis remains unimpaired by any of its critiques